Investigation of structure, mechanical, and shape memory behavior of thermally activated poly(?-caprolactone): azide-functionalized poly(vinyl chloride) binary polymer blend films - Pekdemir, Mustafa Ersin; Qader, Ibrahim Nazem; Oner, Ecem; Aydogmus, Ercan; Kok, Mediha; Dagdelen, Fethi (Springer Heidelberg, 2021)
Like alloys in metallurgy, polymers are blended to obtain new characteristics, which is important to extend their application area. In this study, three different compositions of azide-functionalized poly(vinyl chloride)-PVC-N-3 and poly(epsilon-caprolactone)-PCL were blended. Physical properties, such as mechanical and thermal behavior of the blends, were investigated through the tensile test, DSC, and TGA. Also, a blended polymer with equal participation of each constituent was trained to determine the shape memory behavior of the sample. The results showed that PVC-N3 and PCL were completely miscible; therefore, all physical properties are somewhere between the pure polymers. The blend with only 50% PCL, as an example, still kept its shape memory behavior; additionally, the blended polymers partially achieved crystalline behavior by adding PCL to the PVC-N3. The tensile test also showed that the modulus of toughness and other mechanical behavior depends on the compositional ratio of the polymers. Consequently, the miscibility of the PCL and PVC-N-3 enhances the physical properties of both polymers as a function of composition. Graphic abstract
Keywords: Nanocomposites; Nanoparticles; Morphology; Networks; Lipase